From soundscapes to societies: investigating gamelan's cultural impact through the socio-karawitanology paradigm - Sularso Sularso; Bao Hanshi; Qinyu Yu (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
This article investigates the auditory environment, known as